دراسة لآلية تأسيس وحدة للتعليم الالكتروني في الجامعات العراقية (Al-Mansour Journal, 2023)
The revolution of E-learning is currently endorsing great positive impact in the world of education, and will continue to do so in the future.Many countries are spending vast amount of money in E-learning in order to have full benefits of this field. Statistics shows that the size of E-learning market is about $11 Billion annually with 60-70% of its growth in the USA. While the amount spent in Arab world during the past few years is $15 million and expected to rise 50-60 million dollars in the coming few years. The UAE dominates the Arab world, in the field of E-learning, as far as spending and investment which reached about $6 million in 2003 and expected to reach $24 million by the end of 2008.A practical overview of the overall possibilities that are embedded in the field of E-learning, which can be learned from past and current experiences of countries who pioneered the field of E-learning, for which regulated plans that can be put so as to articulate more subtle future trends that can be helpful in applying E-learning all over the world.A quick look at the current situation of E-learning in Iraq will unleash severe weakness, in which there is no such thing as E-learning. There is actually no acting board that is taking care of things of concern to E-learning. All current educational principles are based on the old traditional educational standards, and there are many who encourage such notions.This paper is to dwell in matters that concern E-learning and how to infuse such teaching in the structure of the Iraqi educational system with it being as an aid not a replacement to the current system